Sinergi Religi dan Kesehatan Holistik: Implementasi Tri Hita Karana di Pura Luhur Batu Panes Desa Mangesta Kecamatan Penebel Tabanan - Putriyani Dewi, Ni Luh PT.; Wisuda, Pande Putu Toya; Sinarsari, Ni Made; I Nyoman Agus Pradnya Wiguna; Kartika, I Gusti Agung Ayu Kartika (Sevanam: Jurnal Pengabdian Masyarakat, 2025)
The concept of Tri Hita Karana is a philosophy of Balinese society that emphasizes the balance between human relationships with God (Parahyangan), fellow humans (Pawongan), and nature (Palemahan). This principle is not only applied in social and cultural life but also in community-based holistic health practices. This study aims to analyze the implementation of Tri Hita Karana in health services at Pura Luhur Batu Panes, Desa Mangesta, Kecamatan Penebel, Tabanan. The study employs a qualitative method with a case study approach based on community service activities that integrate religious, social, and natural resource utilization aspects. The findings indicate that the Parahyangan aspect is reflected in religious rituals and the use of sacred hot springs as a healing medium. The Pawongan aspect is evident in the community’s solidarity and mutual cooperation in health services, such as acupressure therapy, health screenings, and herbal distribution. Meanwhile, the Palemahan aspect is manifested in the preservation of the temple environment and the use of traditional medicinal plants as a form of natural treatment. This study affirms that the Tri Hita Karana approach not only improves physical health but also enhances the spiritual and social well-being of the community. Thus, the integration of religious values in health services can serve as a sustainable holistic model in maintaining life balance.